2010
DOI: 10.1007/s00432-010-0848-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term interferon-α treatment suppresses tumor growth but promotes metastasis capacity in hepatocellular carcinoma

Abstract: IFN-α has janus face of consistently suppressing HCC growth, however, promoting tumor metastasis capacity, which is of clinical indication for the scientific administration of IFN-α and the similar antiangiogenesis drugs for their dual effect on tumor growth and metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…It has been reported that MHCC97L and HepG2 cells surviving oxaliplatin treatment show enhanced migration and invasion in vitro and increase metastasis to the lung when reinoculated into nude mice [19]. Similar results have been observed in our previous study that IFN-α had contrasting aspects of consistently suppressing HCC growth but also promoting tumor metastasis capacity [20]. Therefore, it is urgent to investigate new agents with robust inhibitory effects on both HCC growth and metastasis.…”
Section: Discussionsupporting
confidence: 77%
“…It has been reported that MHCC97L and HepG2 cells surviving oxaliplatin treatment show enhanced migration and invasion in vitro and increase metastasis to the lung when reinoculated into nude mice [19]. Similar results have been observed in our previous study that IFN-α had contrasting aspects of consistently suppressing HCC growth but also promoting tumor metastasis capacity [20]. Therefore, it is urgent to investigate new agents with robust inhibitory effects on both HCC growth and metastasis.…”
Section: Discussionsupporting
confidence: 77%
“…CTCs were enumerated by flow cytometry and expressed as percent CTCs/TV (%) [6]. Twelve mice (IE 1, n = 6) were sacrificed 2 d after resection to examine CTCs shortly after PR.…”
Section: Methodsmentioning
confidence: 99%
“…The surgery is actually palliative resection (PR), owing to the existence of satellites and microvascular invasion, and these residual tumor nests can actually be stimulated to grow by the PR [2,3]. Although several treatments, such as interferon-alpha and sorafenib, have been proposed to diminish relapse [4,5], prometastatic side effects of these options have also been observed [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…Third, whether IFN is accompanied by other effects should be investigated. Zhuang et al [50] reported that IFN-α treatment significantly suppresses tumor growth of HCC but relatively increases the number of circulating tumor cells. This result might be attributed to the enhanced tumor hypoxia as well as the up-regulation of metastasis-related genes, such as HIF-1α, c-met, u-PA, PDGF-A, and IL-8.…”
Section: Discussionmentioning
confidence: 99%